Polymer, metal and laser interactions in metal additive manufacturing using powder sheet - Sasnauskas, Arnoldas (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2026)
Metal Additive manufacturing using Powder Sheets (MAPS) is an emerging approach designed to address key limitations associated with traditional powder-based additive manufacturing technologies. Conventional methods such as laser powder bed fusion (LPBF) struggle with powder waste and recyclability, partially due to the mixing of different powders, which complicates separation and renders multi-material printing less economically viable. Furthermore, the handling of metallic powders posses an inherent safety risk to operators due to their inhalation and combustion hazards. MAPS addresses these challenges by implementing a composite feedstock consisting of metallic powders embedded within a polymer binder matrix, forming a powder sheet. This composite is selectively laser melted to fabricate metallic 3D printed structures. The aim of this study is to enhance understanding of the interactions among the polymer binder, metal powder, and laser during the laser melting process of a powder sheet composed of CrCoMnFeNi metal powder and polycaprolactone polymer binder. The powder sheet exhibits a range of mechanical and physical properties depending on the polymer binder content and sheet thickness, with yield strengths between 0.3 -+ 0.1 MPa and 1.7 -+ 0.5 MPa and powder packing density 0.18 -+ 0.05 to 0.58 -+ 0.04. These properties directly influence the material deposition rate and how likely the sheet is to fail during MAPS. The powder sheet with a higher polymer concentration tends to experience ligament-style failure. In some circumstances (likely at higher speeds and intense plume generation) sections of the powder sheet will detach, removing material from the scan path and promoting laser re-scanning of the previous layer (ultimately remelting and smoothing the surface, and causing deposition inefficiency). In addition this work finds that 27.8 -+ 3.8% of the carbon present in the powder sheet is absorbed by the bulk material during MAPS, irrespective of the polymer concentration in the composite. Most of the carbon is lost due to polymer vaporisation and gas formation, which generate a significant plume and cause effects such as particle detachment and increased laser plume interactions. At high laser scan speeds (and therefore lower volumetric energy), carbon in the form of a black residue remains on the print surface meaning there was insufficient energy to absorb or blow away all the carbon. The carbon absorbed and interactions with the generated polymer plume across a variety of laser scanning speeds produces melt pools with larger depth-to-width ratios than typical powder. Across the energy densities studied there is an average 41 -+ 18% increase in depth-to-width variation between MAPS and loose powder printing. In addition the alloy fabricated using MAPS exhibits more refined microstructure and expanded face center cubic (FCC) lattice structures, indicators of grain pinning and carbon induced lattice strain. In result the yield strength, ductility and hardness all see improvements, where dramatic decrease of ductility is exhibited at polymer binder concentrations above 10 wt.% (in the powder sheet). These results make it clear that there are notable drawbacks (chemical alternations to the alloy and deposition inefficiency) with the MAPS process associated with the polymer binder. The latter part of this work presents a new process where the polymer is ablated by a low energy scan before a high energy laser melt to mitigate the drawbacks while providing a new opportunity in fabricating functionally graded chemical composition. Optimised parameters of this process can increase deposition efficiency up to 60 -+ 7% by mitigating spatter effects. In addition, majority of the carbon can be removed to greatly reduce the hardness of the material from 353 -+ 5 HV1 to a softer 241 -+ 7 HV1. On average there is a 51.5 -+ 16.3% reduction in carbon content in the alloy depending on the volumetric energy density and spot size utilised. Underlying mechanisms responsible for these changes were studied in depth by conducting simulations of the applied spot temperature and high-speed imaging of the plume and spatter generation. The ablation offers an opportunity to manufacture a functionally graded material with a minimal bleed zone. Applications for this can be realized in high performance components that require varied mechanical properties such as hard on outer surfaces and ductile cores.
APPROVED
Keywords: Composite; Polymer; Laser; Additive Manufacturing; Cantor Alloy